Upaya Pembentukan Mediasi Komunitas Berbasis Kearifan Lokal Di Dusun Ranget Desa Suranadi Kabupaten Lombok Barat - Hilman Syahrial Haq (UNIVERSITAS MUHAMMADIYAH MATARAM, 2022)
Community mediation based on local wisdom is required as a means to materialize the orderliness in a society, particularly after a dispute occurs, especially with the complexity of problems in the judicial institution such as the accumulation of cases that can slow down the distribution of justice and legal certainty for those in dispute. This service activity was carried out using the discussion method when making peace over a dispute in Ranget Sub Village. The results show that Ranget Sub Village has local wisdom that can be institutionalized into community mediation to subsequently strengthen the results of the peace, so that, it has legal force as a permanent court decision. This effort is possible by the issuance of the West Nusa Tenggara Provincial Regulation Number 9 Year 2018 concerning Bale Mediasi NTB (West Nusa Tenggara Mediation Board).